Contributions of cognitive behavioral therapy to the treatment of anxiety symptoms during the COVID-19 pandemic - Lages Vieira Passos, Ádilo (2023)
This study aimed to carry out an integrative review of the literature on the contributions of CBT to the treatment of anxiety symptoms in the context of the COVID-19 pandemic. To this end, an integrative literature review was carried out in the PubMed, Scopus, and Web of Science databases, using the descriptors “Cognitive Behavioral Therapy”, “Anxiety”, and “COVID-19”, with the following primary filters: articles in English which were empirical research published between 2019 and 2021. Based on the search criteria, three articles were selected for analysis; these were, above all, randomized clinical trials of a quantitative nature, originating in Sweden and investigating the implementation of CBT in internet-based interventions, from the offer of booklets psychoeducational, recorded